2003
DOI: 10.1246/cl.2003.1156
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Decomposition of Acetaldehyde under Visible Light Irradiation over La3+ and N Co-doped TiO2

Abstract: La3+ and N co-doped TiO2, which contained paramagnetic N species, decomposed acetaldehyde under visible light irradiation. The number of the paramagnetic N species seemed to control the absorption of visible light and the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 5 publications
7
59
0
Order By: Relevance
“…[23][24][25] Figure 4 presents the UV-Vis diffuse reflection absorption spectra of TiO 2 , Cr/S/TiO 2, and Cr/S/TiO 2 -HGM. The absorption wavelength of pure TiO 2 is less than 400 nm, and bulk TiO 2 is a wide band gap semiconductor with a band gap of 3.2 eV (387 nm) for anatase.…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…[23][24][25] Figure 4 presents the UV-Vis diffuse reflection absorption spectra of TiO 2 , Cr/S/TiO 2, and Cr/S/TiO 2 -HGM. The absorption wavelength of pure TiO 2 is less than 400 nm, and bulk TiO 2 is a wide band gap semiconductor with a band gap of 3.2 eV (387 nm) for anatase.…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…It was reported that nitrogen and lanthanum codoped TiO 2 nanoparticles showed a superior photocatalytic activity on degradation of methyl orange under visible light irradiation compared to N-doped or La-doped TiO 2 [10,11]. The N-F codoped TiO 2 Doping TiO 2 with lanthanide element has attracted increasing attention due to their special 4f electron configuration [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Sakatani et al 15 reported that the N and La codoped TiO 2 photocatalyst which prepared by means of polymerized method could degrade acetaldehyde under visible light irradiation. Zhao et al 16 reported that the spectral response and photocatalytic efficiency could be improved by co-doping with nonmetal boron and the metal oxide Ni 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%